Cultivating the Value of Religious Tolerance Through Habib Ja’far’s Preaching Message in YouTube Content “Login” Episode 21 - M. Sandi Bagus Prayogo,; Hasyim Iskandar,; Song Doojin, (Mediakita, 2025)
This research aimed to analyze the cultivation of the religious tolerance value through Habib Ja’far’s preaching messages and their impact on the audiences. The primary data sources in this research were the YouTube content “Login” episode 21 and the comments from its audiences. Meanwhile, the secondary data sources were several previous research results and relevant references. This research utilized a descriptive qualitative approach by combining observation and documentation techniques, also analysis techniques by Eriyanto. The results of this research indicated that: 1) Habib Ja’far cultivated the values of religious tolerance through bil-hal and bil-hikmah preaching wrapped in bil-lisan preaching, in the form of inclusive narratives, humorous approaches, interactive dialogues that prioritize empathy, and concrete actions. Among these values of tolerance are: a) religious differences were not a reason to break the bond between parents and children, b) differences in religion and beliefs were not obstacles in establishing harmonious relationships between parents and children, and c) religion was a choice, not inherited, and there was no compulsion in religion. 2) There were 92.55% of audience responses indicating positive acceptance of the concept and practice of religious tolerance presented and exemplified by Habib Ja’far, Onad, Mama Elly, and her children. The conclusion of this study confirms that building religious tolerance through digital da'wah methods is effective enough and relevant to the needs of the digital generation.